2005
DOI: 10.1521/suli.2005.35.6.646
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Suicide Attempts of Lesbian, Gay, and Bisexual Youth

Abstract: In this study predictors of serious suicide attempts among lesbian, gay, and bisexual (LGB) youth were examined. Three groups were compared: youth who reported no attempts, youth who reported attempts unrelated to their sexual orientation, and youth whose attempts were considered related to their sexual orientation. About one third of respondents reported at least one suicide attempt; however, only half of the attempts were judged serious based on potential lethality. About half of all attempts were related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(126 citation statements)
references
References 31 publications
6
112
0
7
Order By: Relevance
“…Parental awareness of a child's homosexual orientation occurs at an earlier age for gender nonconforming individuals. Such individuals are also at greater risk for parental verbal victimization (D'Augelli et al, 2005) which might increase the socially-induced damage done to the self-esteem of gender atypical children (Aubé & Koestner, 1992;Egan & Perry, 2001). Longitudinal research could differentiate the negative impact of harassment based on CGNC alone, harassment based on (presumed) homosexuality, and the impact of both forms together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental awareness of a child's homosexual orientation occurs at an earlier age for gender nonconforming individuals. Such individuals are also at greater risk for parental verbal victimization (D'Augelli et al, 2005) which might increase the socially-induced damage done to the self-esteem of gender atypical children (Aubé & Koestner, 1992;Egan & Perry, 2001). Longitudinal research could differentiate the negative impact of harassment based on CGNC alone, harassment based on (presumed) homosexuality, and the impact of both forms together.…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of LGB youth (D'Augelli et al, 2006), the impact of CGNC on mental health (trauma symptoms and posttraumatic stress disorder) was comparable between the sexes. Furthermore, parental discouragement of CGNC behavior was characteristic for both GB and LB suicide attempters compared to non-attempters (D'Augelli et al, 2005).…”
Section: Childhood Gender Nonconformity As Precursor Of Later Suicidamentioning
confidence: 92%
“…46 Another study found that suicide attempts among sexual minority youth were positively correlated with parental psychological abuse of the child, being considered gender atypical in childhood by parents, and parental efforts to discourage gender atypical behavior. 47 Sexual minority teens who run away or are put out by their families after acknowledging their sexuality are often victimized, which leads to further mental health issues. Homeless LGBTQ teens are more likely than heterosexual teens to meet criteria for each of 4 mental disorders: major depressive disorder, post-traumatic stress disorder, substance abuse, and conduct disorder.…”
mentioning
confidence: 99%
“…1,13,17,23 Sexual minority youth suffer higher rates of depression and were more than twice as likely to have considered suicide. 1,13,17,[24][25][26] Protective factors against depression, suicidal ideation, and suicide attempts included family connectedness, caring adults, and school safety. 27 Referral for "conversion" or "reparative therapy" is never indicated; therapy is not effective and may be harmful to LGBTQ individuals by increasing internalized stigma, distress, and depression.…”
Section: Definitionsmentioning
confidence: 99%